Translingual identity: Perpetual foreigner stereotype of the Eastern-European immigrants in Australia - Tankosic, Ana (2022)
Translingual identity, as a part of the trans-paradigm, refers to linguistic, sociocultural, ethno-racial, and religious practices, which are negotiable, fluid, and in motion, transcending mainstream boundaries. This paper expands the translingual literature from the perspective of sociolinguistic disparities of culturally and linguistically diverse Eastern-European immigrant women in Australia, as they become victims of the perpetual foreigner stereotype in their host communities. Using the linguistic ethnography methods, such as open ethnographic observation and semi-structured interview, the study reveals that due to biographical accent, name, and the country of origin, as aspects of translingual identity - Australian-by-passport, those women become the victim of the perpetual foreigner stereotypes, such as 'perceived as different' and 'Russian bride, ' which led to their feelings of inferiority and social inequality. By expanding the scope of the translingual identity and how it is perceived in Australia, this study provides a necessary contribution to the translingual literature, while simultaneously advocating for the quality of life and justice for translingual immigrants in their new home.